2013
DOI: 10.1590/s0100-83582013000400006
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous tissue extracts of Conyza canadensis inhibit the germination and shoot growth of three native herbs with no autotoxic effects

Abstract: -Conyza canadensis is a widespread weed species forming dense populations in most regions of China. Petri dish bioassays with aqueous extracts of the aboveground parts and roots of C. canadensis at three concentrations (0.05, 0.1, and 0.2 g mL -1) were undertaken to investigate the autotoxic effects of C. canadensis, and the possible effects on three dominant native weed species, Plantago asiatica, Digitaria sanguinalis and Youngia japonica. The results showed that seed germination and the shoot length of thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
(35 reference statements)
1
8
2
Order By: Relevance
“…Consistent with previous reports (Djurdjević et al 2011;Hu & Zhang 2013), our results indicated that C. canadensis exerts significant allelopathic effects on seed germination and growth of L. sativa. Our findings are consistent with the Novel Weapons Hypothesis, i.e., that some invaders are successful because they possess novel biochemical weapons that function as unusually powerful allelopathic agents, or as mediators of new plant-soil microbial interactions (Callaway & Ridenour 2004).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with previous reports (Djurdjević et al 2011;Hu & Zhang 2013), our results indicated that C. canadensis exerts significant allelopathic effects on seed germination and growth of L. sativa. Our findings are consistent with the Novel Weapons Hypothesis, i.e., that some invaders are successful because they possess novel biochemical weapons that function as unusually powerful allelopathic agents, or as mediators of new plant-soil microbial interactions (Callaway & Ridenour 2004).…”
Section: Discussionsupporting
confidence: 93%
“…Some plants successfully invade certain environments because they can release toxic chemicals and thereby pose an allelopathic eff ect on seed germination and growth of co-occurring species (Djurdjević et al 2011;Hu & Zhang 2013;Wang et al 2016). Plant invasions can occur in diff erent degrees (i.e., diff erent quantitative cover classes) in colonized ecosystems (Seastedt & Pyšek 2011;Wang et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential allelopathic effects are often tested through bioassays, typically by testing the effects of plant tissue extracts on the germination of a target species (e.g. Pisula and Meiners 2010a, b;Hu and Zhang 2013a;Meiners 2014). A bioassay experiment was selected for our study as it allowed us to investigate potential effects of the entire suite of plant biochemical exudates giving us a broader view of allelopathic potential of our study species (Meiners 2014).…”
Section: Germination Experimentsmentioning
confidence: 99%
“…The competition for soil resources, mainly water and soil nutrients, may not have had significant effects due to the fact that these factors are not limiting due to soil characteristics (soil fertility and water retention capacity) and periodic irrigations on this experiments. Thus, changes in soil competition conditions may be due to other associations between the roots as allelopathic effects (HU & ZHANG, 2013). However, the spatial occupation ability of the roots is of primary importance in the competition for soil resources, and the relative growth rate, biomass, root hair density, and surface area are the characteristics necessary for a plant to have a good competitive ability (CASPER & JACKSON, 1997).…”
Section: Resultsmentioning
confidence: 99%